Strategi Pemberian Tugas Praktikum dalam Pembelajaran PAI untuk Meningkatkan Minat Belajar Peserta Didik di SMP Negeri 1 Barebbo - Yunus, Andi Muhammad (JURNAL AL-QAYYIMAH, 2020)
The subject matter examined in this thesis is PAI learning in the state Junior high School 1 Barebbo, interest in learning and the strategy of giving the practical task in PAI learning to increase the learning interest of students at SMP Negeri 1 Barebbo District Barebbo Kab. Bone.This research is a field research. This type of research is a qualitative descriptive by using normative theological approaches, pedagogic approaches, sociological approaches, psychological approaches. Data collection method used is qualitative research category then the data needed is qualitative data consisting of primary data and secondary data.The results showed that 1) PAI lessons not only drove learners to master a variety of Islamic studies, but PAI further emphasized how learners are able to master the Islamic Studies and can practice it in everyday life in the midst of society. 2) teachers in teaching should pay attention to the character of his different students. Teachers provide attention, guidance, and variety of learning methods, strategies, media used in the teaching and learning process. 3) The strategy of giving practicum assignments in schools is increasing the interest of learners because of the formation of habits that are done and add accuracy, as well as the speed of execution, utilization of habits that do not require concentration in the implementation, increasing the motivation and learning passion of students and increase the motivation and passion of students because the work is done to give new challenges and facilitate and deepen understanding That are being worked on.